MARKET SAMPLE SURVEY OF CROCUS SATIVUS LINN. TO ASSESS THE GENUINITY FOR USING ANTIOXIDANT ACTIVITY, TOTAL PHENOLIC CONTENT AND HIGH-PRESSURE THIN LAYER CHROMATOGRAPHY USING DETECTION OF FLAVONOIDS - ATHIRA, K. R.; BINU, T. V. (International Journal of Current Pharmaceutical Research, 2019)
Objective: Herbalism is a traditional medicine or folk medicine practice based on the use of plants and plant extracts. Many of the drugs used in conventional medicine are dried from herbs. Despite the fluctuation in prices in international markets, saffron was still remained the most expensive spice. The main aim of this study is to examine the antioxidant activity, total phenolic content, high-pressure thin layer chromatography using flavanoid analysis and adulteration detection of saffron. Crocus sativus. Linn is a perennial stemless herb of the Iridaceae family. Saffron stigmas of sample1, sample2, sample3and sample4 are collected from different rates of the market sample from Thrissur district, sample5 collected from the Oushadhi premises, and it is collected from Himachal Pradesh. Methods: In this study detecting the antioxidant activity, total phenolic content, high-pressure thin layer chromatography using flavanoid analysis of different samples of saffron stigmas. The extracts were prepared by using ethanol as a solvent. Results: Safranal is present only in s5 sample. It is the main essential volatile oil responsible for the saffron characteristic such as odour. Phenolic content is varied in different market samples. The amount of phenolic compounds in the saffron extract was determined using the Folin-ciocalteau reagent. Total phenolic content is the help to detect the pure and fake saffron. The phenolic content is higher in S5. Sample S5 showed 0.737 mg/ml phenolic content. Lowest level of phenolic content in sample S3. Sample S3 showed 0.0887 mg/ml phenolic content. Sample S4 showed 0.564 mg/ml total phenolic content. Sample S1 showed 0.416 mg/ml total phenolic content and sample S2 showed 0.267 mg/ml phenolic content. Antioxidant activity is higher in sample s5. and it is different in different market samples. Sample 5 stigma posses higher antioxidant activity. Sample S5 showing 14.88% antioxidant activity in 100 mg/ml concentration, 7.26% in 80 mg/ml concentration, 2.23% in 60 mg/ml concentration, 2.21% in 40 mg/ml and 1.01% in 20 mg/ml concentration. Sample S3 showed the lower antioxidant activity in 0.1% in 60 mg/ml concentration and 0.1% in 80 mg/ml. Ascorbic acid standard showing 14.89% in 100 mg/ml concentration, 7.26% in 80 mg/ml concentration, 4.56% in 60 mg/ml concentration, and 3.1% in 40 mg/ml concentration, and 1% in 20 mg/ml concentration. Flavonoid content is different in different samples. It is present highly present in sample s1 and s5. sample s3 do not contain the Flavanoid. The quality of the samples depend on the price values. Conclusion: The authenticity of saffron is an extremely important matter for the industry and for the consumers in view of security and protection,quality assurance, active properties and last but not least, economic impact. Despite the fluctuation in prices in international markets, saffron was and still remains the most expensive spice. The genuine saffron samples possess higher price value. The fake saffron available in the market with lower price value. The quality of the saffron depends upon the price values. These observations would be of immense value in the botanical identification and standardization of the drug in crude form and would help to distinguish the drug from its other spices.